Immune-Modulating Perspectives for Low Frequency Electromagnetic Fields in Innate Immunity - Rosado, Maria Manuela; Simkó, Myrtill; Mattsson, Mats-Olof; Pioli, Claudio (Frontiers in Public Health, 2018)
In recent years, the effects of electromagnetic fields (EMFs) on the immune system have received a considerable interest, not only to investigate possible negative health impact but also to explore the possibility to favorably modulate immune responses. To generate beneficial responses, the immune system should eradicate pathogens while “respecting” the organism and tolerating irrelevant antigens. According to the current view, damage-associated molecules released by infected or injured cells, or secreted by innate immune cells generate danger signals activating an immune response. These signals are also relevant to the subsequent activation of homeostatic mechanisms that control the immune response in pro- or anti-inflammatory reactions, a feature that allows modulation by therapeutic treatments. In the present review, we describe and discuss the effects of extremely low frequency (ELF)-EMF and pulsed EMF on cell signals and factors relevant to the activation of danger signals and innate immunity cells. By discussing the EMF modulating effects on cell functions, we envisage the use of EMF as a therapeutic agent to regulate immune responses associated with wound healing.